Erythrocyte membrane sulfatide plays a crucial role in the adhesion of sickle erythrocytes to endothelium - Zhou, Zhou; Thiagarajan, Perumal; Udden, Mark M.; López, José A.; Guchhait, Prasenjit (Thrombosis and Haemostasis, 2011)
Enhanced adhesion of sickle erythrocytes to the vascular endothelium and subendothelial matrix is fundamental to the development of vascular occlusion in sickle cell disease. Erythrocyte membrane sulfatide is implicated in the pathogenesis of vasoocclusive crises in sickle cell disease (SCD) patients. Because previous evidence linking sulfatide to cell adhesion has largely been circumstantial due to a lack of reagents that specifically target sulfatide, we used two sulfatide-specific strategies to address the role of erythrocyte membrane sulfatide in sickle cell adhesion to the vascular endothelium: a single-chain fragment variable chain (scFv) antibody against sulfatide as well as cerebroside sulfotransferase-deficient mice incapable of synthesising sulfatide. The sickle erythrocytes from mice and humans adhered at a greater extent and at higher shear stresses to activated endothelium than normal erythrocytes, and approximately 60% of the adhesion was prevented by the anti-sulfatide scFv. Similarly, the extent of adhesion of sulfatide-deficient erythrocytes was lower than normal erythrocytes. These findings suggest an important role for membrane sulfatide in sickle cell disease pathophysiology.
Keywords: Adhesion molecules; endothelial cells; extracellular matrix; cell-matrix interactions